2021
DOI: 10.14202/vetworld.2021.545-550
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of elephant endotheliotropic herpesvirus infection in wild and captive Asian elephants in Thailand: Investigation based on viral DNA and host antibody

Abstract: Background and Aim: Elephant endotheliotropic herpesvirus (EEHV) is a serious disease, threatening the life of young elephants. Many elephants have been infected with no clinical signs and may serve as carriers spreading this disease. It is important to monitor the disease through clinical signs and molecular diagnosis. In this study we investigated the occurrence of EEHV and the efficiency of different techniques used to monitor EEHV infection in various samples and populations of Asian elephants. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…A serological study for EEHV detection using ELISA tests has been implemented in elephants in European zoos, as well as those living in captivity in North America and Thailand, using EEHV structural proteins such as gB and gH/gL [ 21 , 23 , 24 ]. In contrast to the results of previous reports, however, the seropositivity results for the EEHV-DNApol ELISA test in this study were lower than those of previous reports, indicating 42–44% seropositivity for EEHV-gB ELISA in Thai captive elephants [ 22 , 24 ]. Moreover, a serosurvey of EEHV infection using the EEHV-gH/gL ELISA revealed that more than 97% of elephants from European zoos were determined to be EEHV seropositive [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A serological study for EEHV detection using ELISA tests has been implemented in elephants in European zoos, as well as those living in captivity in North America and Thailand, using EEHV structural proteins such as gB and gH/gL [ 21 , 23 , 24 ]. In contrast to the results of previous reports, however, the seropositivity results for the EEHV-DNApol ELISA test in this study were lower than those of previous reports, indicating 42–44% seropositivity for EEHV-gB ELISA in Thai captive elephants [ 22 , 24 ]. Moreover, a serosurvey of EEHV infection using the EEHV-gH/gL ELISA revealed that more than 97% of elephants from European zoos were determined to be EEHV seropositive [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Viral genome detection includes PCR, qPCR, loop-mediated isothermal amplification (LAMP), and in situ hybridization [ 12 , 13 , 14 , 15 , 16 , 17 ]. Viral protein and viral particle detection involves histopathology, Western immunoblotting, immunohistochemistry, immunofluorescence, and electron microscopy [ 2 , 3 , 4 , 18 , 19 ], while anti-EEHV antibody detection involves enzyme-linked immunosorbent assay (ELISA) and the luciferase immunoprecipitation system (LIPS) [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risks posed by the EEHVs to captive and wild Asian elephants are widely recognized. Surveys of captive, semi-captive, and, to a lesser extent, wild elephants have been conducted in several countries, and surveillance for captive and semi-captive elephants have been developed to suit local conditions [2,14,15]. China is an Asian elephant range country and has a captive Asian elephant population; however, the EEHV status of China's wild and captive elephants is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used PCR assays to detect active infections in the elephants that we studied instead of screening for infection using serology, as the only population of elephants that we could obtain blood samples from was the captive population housed at the Wild Elephant Valley. Using molecular screening also allowed us to compare the sequences of the detected types and subtypes to those reported in other countries [15]. Screening elephants with PCR assays, however, has its limitations, as it only detects elephants with active infections and not latently infected elephants that are not viremic or shedding EEHV.…”
Section: Molecular Versus Serological Screening Of Asian Elephants Fo...mentioning
confidence: 99%